Answer: C and D
Step-by-step explanation:
The factor theorem tells us that if we evaluate a polynomial [tex]p(x)[/tex] at [tex]x=a[/tex] and the answer is 0, then [tex](x-a)[/tex] is a factor of [tex]p(x)[/tex].
So we can check,
[tex]x=2[/tex] from [tex](x-2)[/tex]
[tex]x=1[/tex] from [tex](x-1)[/tex]
[tex]x=-1[/tex] from [tex](x+1)[/tex]
and
[tex]x=-2[/tex] from [tex](x+2)[/tex]
and see which gives us 0. For those that give 0, that respective expression is a factor of the binomial expression given.
[tex]4(2)^{3}+9(2)^{2}-(2)-6\\=60[/tex]
[tex]4(1)^{3}+9(1)^{2}-(1)-6\\=6[/tex]
[tex]4(-1)^{3}+9(-1)^{2}-(-1)-6\\=0[/tex]
[tex]4(-2)^{3}+9(-2)^{2}-(2)-6\\=0[/tex]
The last 2 gives us 0. Hence, [tex](x+1)[/tex] and [tex](x+2)[/tex] are factors of [tex]4x^{3}+9x^{2}-x-6[/tex]. Answer choices C and D are correct.